Namibia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues paper analyzes unemployment and education in Namibia. Using the Afrobarometer Project survey data, the paper develops some stylized facts about the Namibian labor market, focusing on the link between education, earnings, and unemployment. The paper finds that unemployment probabilities depend on the level of education. The paper also describes the main features of poverty in Namibia and assesses the appropriateness of current as well as potential policies to alleviate poverty and reduce income inequality over time.